Molecular pathology : the molecular basis of human disease - Coleman, William B.; Tsongalis, Gregory J. (Academic Press, 2009)
Most "pathology" textbooks cover diseases and disease processes from the perspective of description (what does it look like and what are its characteristics), risk factors, disease-causing agents, and to some extent, cellular mechanisms. However, these books typically contain very sparse coverage (if any at all) of molecular mechanisms of disease. The reason for this is partially historical - most major forms of disease have been known for a long time, but the molecular basis of these diseases are not always known or have been elucidated only recently. Nevertheless, our overall understanding of the molecular and genetic mechanisms of the pathogenesis of most major human diseases has been advancing at a significant pace over the last two decades. As the molecular basis of human disease becomes better characterized, and the implications for understanding the molecular basis of disease becomes realized through improved diagnostics and treatment, there is a need for a new textbook where molecular mechanisms represent the focus. Molecular Pathology focuses on the molecular basis of major human diseases and disease processes, presented in the context of traditional pathology, with implications for translational molecular medicine. Molecular Pathology is appropriate as a classroom teaching tool for medical students, biomedical graduate students, and some allied health students. In addition, it should be used as a reference book for practicing basic scientists and physician scientists that perform disease-related research. Further, this textbook will be valuable for pathology residents and other postdoctoral fellows who need to advance their understanding of molecular mechanisms of disease beyond what they learned in medical/graduate school. * Exam Master web site will host "Self-assessment" questions that students can use to study for the molecular section of the board exam * Companion Web Site - would host a complete set of PowerPoint slides: to include images from the book and additional images for teaching; course materials; lecture materials * Teaches from the perspective of "integrative systems biology," which encompasses the intersection of all molecular aspects of biology, as applied to understanding human disease * Outlines the principles and practice of molecular pathology: molecular pathogenesis, molecular mechanisms of disease, and how the molecular pathogenesis of disease parallels the evolution of the disease using histopathology * Explains the practice of "molecular medicine" and the translational aspects of molecular pathology: molecular diagnostics, molecular assessment, and personalized medicine.